Group-Based Data Offloading Techniques Assisted by D2D Communication in 5G Mobile Network - Ally, Juma Said (Tanzania Journal of Engineering and Technology, 2022)
Machine type communication devices proposed as one of the substantial data collections in the 5G of wireless networks. However, the existing mobile communication network is not designed to handle massive access from the MTC devices instead of human type communication. In this context, we propose the device-to-device communication assisted a mobile terminal (smartphone) on data computing, focusing on data generated from a correlated source of machine type communication devices. We consider the scenario that the MTC devices after collecting the data will transmit to a smartphone for computing. With the limitation of computing resources at the smartphone, some data are offloaded to the nearby mobile edge-computing server. By adopting the sensing capability on MTC devices, we use a power exponential function to compute a correlation coefficient existing between the devices. Then we propose two grouping techniques K-Means and hierarchical clustering to combine only the MTC devices, which are spatially correlated. Based on this framework, we compare the energy consumption when all data processed locally at a smartphone or remotely at mobile edge computing server with optimal solution obtained by exhaustive search method. The results illustrated that; the proposed grouping technique reduce the energy consumption at a smartphone while satisfying a required completion time. Keywords: Data offloading, K-Means algorithm, hierarchical algorithm, differential entropy, MTC, D2D. Juma Said Ally Department of Electronics and Telecommunications Engineering, College of Information and Communication Technology, Mbeya University of Science and Technology, P.O. Box 131 Mbeya, TANZANIA Corresponding email: jeiside@gmail.com